Existence Results for the Positive Solutions of a Fourth Order Nonlinear Equations on the Heisenberg Group (Journal of Partial Differential Equations, 2000)
In this paper, we give some existence results for a fourth order nonlinear subelliptic equations on the Heisenberg group by the Leray-Schauder degree.